(NnEMECKAQ DIALEKTOLOGIQ (B/s - (NvIRMUNSKIJ(B, (NwIKTOR mAKSIMOWI^s; (NiN(B-(NT QZYKOZNANIQ an sssrs ((NmOSKWA (B;s (Nl(Be(NNINGRAD (B:s (Nan sssr (B,s, 1956)
(NbIBLIOGR(B.: (NS(B. 616 - 627s
(Nan sssr iN(B-(NT QZYKOZNANIQs
Keywords: (NgERMANSKIE QZYKIs